2015
DOI: 10.1093/jxb/eru500
|View full text |Cite
|
Sign up to set email alerts
|

Tracking synthesis and turnover of triacylglycerol in leaves

Abstract: HighlightAnalysis of flux of exogenously supplied [14C]fatty acid in wild-type and mutant Arabidopsis leaves indicates that DGAT1 is the predominant enzyme involved in triacylglycerol synthesis in young leaves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 73 publications
(104 reference statements)
2
32
0
Order By: Relevance
“…In the latter case, the DGAT1 gene exhibited increased expression levels in ambient air, and this was reversed by the 1% CO 2 treatment. This finding reflects the importance of DGAT1 as a major regulator of the TAG biosynthetic pathway in seedling plants, as evidenced by the previous analysis of dgat1 mutants, which display a major reduction in leaf TAG accumulation (Zhang et al, 2009;Tjellström et al, 2015).…”
Section: Mthd Contributes To Photorespirationsupporting
confidence: 79%
“…In the latter case, the DGAT1 gene exhibited increased expression levels in ambient air, and this was reversed by the 1% CO 2 treatment. This finding reflects the importance of DGAT1 as a major regulator of the TAG biosynthetic pathway in seedling plants, as evidenced by the previous analysis of dgat1 mutants, which display a major reduction in leaf TAG accumulation (Zhang et al, 2009;Tjellström et al, 2015).…”
Section: Mthd Contributes To Photorespirationsupporting
confidence: 79%
“…In addition, extensive experimental evidence indicates that free FAs supplied to tissues are sequestered into TAGs (Roughan et al, 1987;Koo et al, 2005;Tjellström et al, 2015). These TAGs undergo substantial and rapid turnover (Tjellström et al, 2015).…”
Section: Tag Turnover Is Increased In Vegetative Tissues Of B Distacmentioning
confidence: 99%
“…These TAGs undergo substantial and rapid turnover (Tjellström et al, 2015). Moreover, the expression of many orthologs presumed to encode enzymes involved in TAG degradation was induced, suggesting that this pathway is highly active (Fig.…”
Section: Tag Turnover Is Increased In Vegetative Tissues Of B Distacmentioning
confidence: 99%
“…The presence of high biochemical activities for TAG synthesis (Dahlqvist et al, 2000) and breakdown (Tjellström et al, 2015) raises an intriguing question of the functional role for TAG metabolism in plant vegetative tissues. Early studies in yeast and mammals showed that TAG accumulation plays a pivotal role in sequestering FFAs (Listenberger et al, 2003) and DAG (Zhang et al, 2003) into lipid droplets and thereby protecting against lipotoxic cell death under cellular conditions of fatty acid overload.…”
mentioning
confidence: 99%